Myocardial Protection in Combined Mitral-Aortic-Tricuspid Valve Diseases Correction under Cardiopulmonary Bypass - Oleksii M. Gurtovenko; Volodymyr V. Popov; Andriy P. Mazur; Oleksandr O. Bolshak (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To determine the optimal option for administering cardioplegic solution for myocardial protection in the correction of combined mitral-aortic-tricuspid valve diseases (CMAT) under cardiopulmonary bypass.Materials and methods. We analyzed the results of surgical treatment of 251 patients with CMAT who were operated on at the National Amosov Institute of Cardiovascular Surgery from 01/01/2010 to 01/01/2023 and in whom 3 ways of applying crystalloid cardioplegic solution was used. There were three comparison groups: group A with antegrade (n = 47), group B with retrograde (n = 56), and group C with combined ante-retrograde administration of crystalloid cardioplegic solution (n = 148).Results. Of the 251 operated patients, 10 died at the hospital stage (mortality rate 3.9%). The level of creatine kinase-MB (CK-MB) (U/L) at cross-clamping time ≤90 minutes for the groups was as follows: 72.3 ± 7.1 (p < 0.05) in group A, 64.0 ± 8.2 in group B, 67.5 ± 7.7 in group C. The level of CK-MB (U/L) at cross-clamping time ≥151 minutes for the groups was as follows: 115.2 ± 18.7 in group A, 97.4 ± 15.8 in group B, 96.3 ± 16.2 in group C. The dynamics of echocardiographic parameters at the stages of treatment were as follows. Group A (mortality rate 4.3%): left ventricular (LV) end-systolic index (mL/m2): 69.1 ± 13.5 (before surgery), 60.3 ± 9.7 (after surgery); left ventricular ejection fraction (LVEF): 51% ± 9% (before surgery), 54% ± 7% (after surgery). Group B (mortality rate 3.6%): LV end-systolic index (mL/m2) 66.5 ± 12.1 (before surgery), 57.4 ± 8.6 (after surgery); LVEF: 50% ± 8% (before surgery), 56% ± 7% (after surgery). Group C (mortality rate 4.1%): LV end-systolic index (mL/m2) 67.8 ± 11.3 (before surgery), 56.2 ± 8.9 (after surgery); LVEF: 50% ± 7% (before surgery), 56% ± 7% (after surgery). The dynamics of echocardiographic parameters at the stages of treatment were better in groups B and C than in group A (p < 0.05). Hospital mortality was lower in groups B and C than in group A (p > 0.05).Conclusions. The three types of cardioplegic solution delivery used in complex pathology of surgical treatment of CMAT demonstrated the adequacy of heart protection using crystalloid cardioplegia. Taking into account certain advantages in the dynamics of restoration of the LV contractility and increase in the level of CK-MB (U/L) on the second day after surgery, groups C and B should be considered optimal compared to group A (p < 0.05). The widespread, branched venous system of the heart allows for adequate use of the retrograde route of cardioplegia delivery and complete penetration of cardioplegic solution into the heart cells, which provides a better clinical effect compared to the isolated antegrade route of crystalloid cardioplegia delivery.